Articulation When Learning Thinking Routines Among Teachers (2018)
The aim of this research was to visualize how learning changes teachers’ thinking routines in a public institution in the Department of Cundinamarca, in order to disclose their reflective thinking and its implications in pedagogical practices. The work was based on a qualitative approach in the form of action research. The main instruments used were the thinking routine “I used to think… Now I think”, and the pedagogic research workshop. They allowed to highlight how transformations in understanding thinking routines focused on didactic sequences from which the development of comprehensions of the subject was addressed. In the first place, through previous knowledge, the fact of knowing the usability and functionality of this strategy, in the second place, a guided research including the approach to various sources, the collaborative and reflective work; and lastly, the transfer of what has been learned at the time of articulating both thinking routines and classroom work with the students.